2021
DOI: 10.1126/sciadv.abj8156
|View full text |Cite
|
Sign up to set email alerts
|

MON-2, a Golgi protein, mediates autophagy-dependent longevity in Caenorhabditis elegans

Abstract: MON-2, which mediates Golgi-endosome trafficking, mediates mitochondrial inhibition–induced longevity by enhancing autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Furthermore, several proteases that are normally being elevated during aging were reduced, particularly starting during mid-age in long-lived daf-2(RNAi) animals (Figure 3A, Supplementary Table 9). Consistent with our proteomics, across six different longevity interventions (dietary restriction, metformin, glp-1, daf-2, isp-1, eat-2) and data sets (Depuydt et al, 2013;Espada et al, 2020;Jung et al, 2021;Koyuncu et al, 2021;Pu et al, 2017), we observed an increase of a subset of cuticular collagens (col-) protein levels, collagen-stabilizing and remodeling enzymes (dpy-18, phy-2, bli-, nas-, zmp-) and a decrease of cathepsin (cpl-, cpz-, cpr-) protease levels (Figure 3B, Supplementary Table 9). We thus propose that longevity interventions mobilize compensatory adjustments counteracting age-related ECM changes, especially in older animals, presumably to maintain homeostasis of the ECM proteins.…”
Section: Longevity Interventions Counteract Age-dependent Ecm Composi...supporting
confidence: 84%
“…Furthermore, several proteases that are normally being elevated during aging were reduced, particularly starting during mid-age in long-lived daf-2(RNAi) animals (Figure 3A, Supplementary Table 9). Consistent with our proteomics, across six different longevity interventions (dietary restriction, metformin, glp-1, daf-2, isp-1, eat-2) and data sets (Depuydt et al, 2013;Espada et al, 2020;Jung et al, 2021;Koyuncu et al, 2021;Pu et al, 2017), we observed an increase of a subset of cuticular collagens (col-) protein levels, collagen-stabilizing and remodeling enzymes (dpy-18, phy-2, bli-, nas-, zmp-) and a decrease of cathepsin (cpl-, cpz-, cpr-) protease levels (Figure 3B, Supplementary Table 9). We thus propose that longevity interventions mobilize compensatory adjustments counteracting age-related ECM changes, especially in older animals, presumably to maintain homeostasis of the ECM proteins.…”
Section: Longevity Interventions Counteract Age-dependent Ecm Composi...supporting
confidence: 84%
“… 87 Similarly, mammalian MON2 (a Golgi protein) is upregulated in long-lived C. elegans , and MON2 is essential for stimulating autophagic flux by activating the Atg8 orthologue GABARAP/LGG-1 in C. elegans to extend longevity. 89 Starvation, lipid restriction, proteins or special amino acid deletions activate autophagy. 90 92 Overactive autophagy in response to fasting is partially regulated by activation of AMPK and SIRT1 activity and inhibition of mTOR activity.…”
Section: Nutrient-associated Molecular Mechanismsmentioning
confidence: 99%
“…MON-2 regulates trafficking between endosomes and the Golgi apparatus (Mahajan et al, 2013). Similarly, TBC-3 is also involved in transport between endosomes and Golgi (Kanamori et al, 2008) and is required for isp-1 lifespan (Jung et al, 2021). While MON-2 appears to be promoting longevity by upregulating autophagy, it is unclear how elevated endosomal MON-2 increases autophagy (Artan et al, 2022; Jung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most well studied mitochondrial mutants in Caenorhabditis elegans are nuo-6 and isp-1 .The nuo-6 gene encodes a subunit of Complex I of the mitochondrial electron transport chain (Yang and Hekimi, 2010), while the isp-1 gene encodes a subunit of the Rieske iron sulfur protein in Complex III of the electron transport chain (Feng et al, 2001). Although a number of studies have identified factors that are important for the long lifespan of these mitochondrial mutants (Baruah et al, 2014; Campos et al, 2021; Harris-Gauthier et al, 2022; Hwang et al, 2014; Jung et al, 2021; Lee et al, 2010; Munkacsy et al, 2016; Senchuk et al, 2018; Walter et al, 2011; Wu et al, 2018; Yee et al, 2014), the mechanism by which mild mitochondrial impairment extends longevity remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%